Pengaruh Kepemilikan Institusional Dan Leverage Terhadap Tax Avoidance - Dwi Listiani; Rudi (EkoPreneur, 2024)
This research aims to analyze the influence of institutional ownership and leverage on tax avoidance. This research was conducted by analyzing the financial reports of companies in the consumer non-cyclicals food & beverage subsector listed on the Indonesia Stock Exchange (BEI) during the period 2019 to 2023. The sample used in this research was 16 companies in the consumer non-cyclicals subsector. food & beverage listed on the Indonesia Stock Exchange (BEI) during the period 2019 to 2023 using purposive sampling techniques. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The variables used in this research are institutional ownership (X1) as the first independent variable, leverage (X2) as the second independent variable and tax avoidance (Y) as the dependent variable. The panel data regression method was used as the research methodology in this study. Analysis of research results using Eviews 12 Student Version Lite software. The research results show that the best model is the Fixed Effect Model (FEM). The results of this research show that institutional ownership partially influences tax avoidance. Leverage partially influences tax avoidance and simultaneously institutional ownership and leverage influence tax avoidance. Keywords: Institutional Ownership, Leverage, Tax Avoidance